2016
DOI: 10.1021/acs.jpcc.6b07588
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Two Methods for Determining Shell Thicknesses of Core–Shell Nanoparticles by X-ray Photoelectron Spectroscopy

Abstract: We evaluated two methods for determining shell thicknesses of core-shell nanoparticles (NPs) by X-ray photoelectron spectroscopy (XPS). One of these methods had been developed for determining thicknesses of films on a planar substrate while the other was developed specifically for NPs. Our evaluations were based on simulated Cu 2p3/2 spectra from Cu-core/Cu-shell NPs with a wide range of core diameters and shell thicknesses. Copper was chosen for our tests because elastic-scattering effects for Cu 2p3/2 photoe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 40 publications
3
18
0
Order By: Relevance
“…Shard assumed that the fourth EAL, L 2 ,b , could be estimated from L 2, b = L 1, a / BC .. We note that eq. (1d) was shown incorrectly in our previous paper 17 but the numerical results therein are correct.…”
Section: Methodsmentioning
confidence: 87%
See 2 more Smart Citations
“…Shard assumed that the fourth EAL, L 2 ,b , could be estimated from L 2, b = L 1, a / BC .. We note that eq. (1d) was shown incorrectly in our previous paper 17 but the numerical results therein are correct.…”
Section: Methodsmentioning
confidence: 87%
“…We consider here two approaches for determining shell thicknesses of core-shell NPs by XPS. First, we extend our earlier evaluation 17 of the Shard 8 equation for measuring shell thicknesses from ratios of photoelectron intensities from the core and shell materials of the NP. Second, we address a necessary simplification generally made in the development of analytical models describing photoelectron intensities from NPs of different sizes and with different shell thicknesses.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…These results support the conclusion that the citrate displacement is not uniquely dependent on the weak Au-COO bond strength (2 kcal/mol) with respect to the strong Au-S bond strength (about 40 kcal/mol). 70,71 In fact, previous studies 36,52 have shown that the structure of the adsorbed citrate molecules plays a fundamental role in the thiols-citrate exchange. Furthermore, in the case of alkanethiols, the coverage was found to be independent on the thiol's chain length.…”
Section: Nanoparticles Functionalizationmentioning
confidence: 99%
“…However, CLS, DLS, and SEM analyses indicate that nanoparticles are aggregating after the third and the fourth centrifugation cycle (Figs. S1 and S2), 71 when changes in distribution index (DI) and poly-distribution index (PDI) are recorded. Moreover, a slight decrease in pH FIG.…”
Section: A Centrifugationmentioning
confidence: 99%